WAQF AN ALTERNATIVE SOURCE FOR POVERTY MITIGATION - Abubakar, Salihu Muhammad (IJRDO - Journal of Social Science and Humanities Research, 2022)
Waqf is one of the Islamic economic tools which served purposely for fighting poverty and enhancing living standard of people. This can be proven from it definition as an Islamic endowment of property to be held in trust and used for a charitable or religious purpose. Various studies have verified on how waqf effectively worked as a tool to provide relief to the needy, improving socio-economic conditions of people, and also serving as a unique poverty alleviation programme. The objective of this paper is to study and discuss the concept of waqf toward the reduction of poverty and improving the poor living standard. The paper adopted qualitative approach through interview and documents research. The finding revealed that there is a positive impact of waqf on poverty mitigation. Yet, special attention needs to be channeled on poor and needy welfare and wellbeing.  Therefore, in other to achieve the objectives of waqf generally, institution handling waqf endowments have to re-double up and channel more attention to the most needy for them to also benefits for its fruits.